The choice of subsidy policy for incentivizing product design for environment. (January 2023) - Wang, Yue; Wang, Zhe; Li, Bangyi; Cheng, Yongbo
Highlights: Three prevailing subsidy schemes for incentivizing product design are presented. The incentive effects of the three subsidy schemes are determined. The supply chain members' preferences for different subsidy schemes are studied. The optimal subsidies of different schemes to maximize social welfare are determined. Two indexes regarding environmental impact are used to find the best subsidy model. Abstract: In order to encourage product design for environment and promote the green products, the government provides three different environmentally friendly subsidies, namely, subsidy for manufacturer's design for environment, subsidy for retailer's sales effort and subsidy for consumer's green consumption. What the incentive effects of the three subsidy mechanisms are and how to choose the appropriate subsidy mechanism deserve further research. To solve those problems, considering the consumer environmental preference, a three-stage Stackelberg model consisted of the government, the manufacturer and the retailer is constructed. The optimal product design for environment and sales effort decisions and profits of the two-echelon supply chain under three kinds of subsidy schemes are compared. And, from the perspectives of social welfare maximization and the marginal environmental impact, the optimal subsidies of three subsidy schemes and the best subsidy scheme are identified, respectively. The results show that the preferences of the manufacturer and the retailer for different subsidy policies depend on the level of three subsidies. The unit profit of the green product and the environmental cost affect not only the existence of optimal subsidy but also the choice of subsidy scheme. Based on the above conclusions, key policy and managerial implications can be generated that the government should set appropriate subsidy scheme and the level of subsidy in accordance with the unit profit of the green product and the environmental cost. Besides, from the perspectives of social welfare and environmental impact, the government should not choose to subsidize the retailer's sales effort. Finally, managers should increase the profit of the green products to obtain higher government subsidy.